THE EFFECT OF WORK STRESS AND JOB ROTATION ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS A MEDIATION ON EMPLOYEES AT PT. MITRA BETON MANDIRI PEKANBARU - Saputra, Ardiansyah Ade; Putra, Ilham Chanra (Jurnal Al-Iqtishad, 2025)
Performance refers to the level of effectiveness and efficiency achieved by individuals or groups in carrying out their duties and obligations. This study aims to determine the effect of work stress and job rotation on employee performance with employee engagement as a mediator in employees at PT Mitra Beton Mandiri Pekanbaru. The population in this study were employees at PT Mitra Beton Mandiri Pekanbaru with a saturated sampling technique totaling 56 respondents who were analyzed using SEM-PLS 4.0. The results of this study indicate that work stress has a negative effect on employee performance and job rotation has no effect on employee performance, while employee engagement has a positive effect on employee performance. Work stress has a negative effect on employee engagement, while job rotation has no effect on employee engagement. Employee engagement can mediate the effect of work stress and job rotation on employee performance. that the employee performance construct can be explained by the variables of work stress, job rotation, and employee engagement as much as 98.3% while the employee engagement construct can be explained by the variables of work stress and job rotation as much as 98.1%.